Advanced photoresist technologies by intricate molecular brush architectures: Diblock brush terpolymer‐based positive‐tone photoresist materials. Issue 2 (22nd August 2014) - Sun, Guorong; Cho, Sangho; Yang, Fan; He, Xun; Pavía‐Sanders, Adriana; Clark, Corrie; Raymond, Jeffery E.; Verkhoturov, Stanislav V.; Schweikert, Emile A.; Thackeray, James W.; Trefonas, Peter; Wooley, Karen L.
<x xml:space="preserve">Abstract</x> The reported diblock brush terpolymer displays the fundamental advantages of high macromolecular and regiochemical control in simultaneous top‐down/bottom‐up construction of advanced positive‐tone photoresist materials. By selective partition the substrate adhesion, surface‐active migration, and chemically‐reactive deblocking functional compositions into the cylindrical polymer brush architectures, large‐areas of vertical alignment of the polymers within thin films are realized. The bottom‐up premeditated system enables effective top‐down lithography to produce near‐molecular pixel resolution (2–3 molecules) at low operation dosage. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>